Interface Effects on Epilayer Surface Density of States by Scanning Tunneling Spectroscopy and Density Functional Theory. Issue 12 (18th September 2019) - Dascalu, Matan; Levi, Rachel; Cesura, Federico; Diéguez, Oswaldo; Goldfarb, Ilan
Abstract: Sub‐nanometric Ni‐silicide films are self‐assembled by solid phase epitaxy of Ni on a vicinal Si(111) surface. The combination of in situ scanning tunneling microscopy and surface electron diffraction with ex situ X‐ray photoelectron spectroscopy allows us to identify θ‐Ni2 Si as the major constituent crystal phase at the overgrown surface. Then scanning tunneling spectroscopy is employed with ab initio electronic structure calculations, to identify the origins of the surface local density of states and use these as a fingerprint for in situ phase identification. The above approach enhances the chemical contrast capability of scanning tunneling microscopy, and offers a useful local probe with atomic resolution for in situ crystal phase identification of ultra‐thin surface structures. Abstract : In‐situ identification of crystal phase and composition of tiny epitaxial A x B y ‐type compound nanostructures in ultra‐high vacuum is extremely challenging. The available chemically sensitive methods lack the required selectivity, while highly selective local probes, such as scanning tunneling microscopy, are chemically insensitive. This work suggests how, by combining scanning tunneling spectroscopy with density functional theory, the missing information can be extracted from the surface local density of states.